The Cult of Statistical Significance: How the Standard Error Costs Us Jobs, Justice, and Lives. - Gleditsch, Kristian Skrede (Journal of Peace Research, 2009)
The article reviews the book "The Cult of Statistical Significance: How the Standard Error Costs Us Jobs, Justice, and Lives," by Stephen T. Ziliak and Deirdre N. McCloskey.